By His Excellency Thomas Pownall, Esq ; captain-general and governour in chief in and over His Majesty's province of the Massachusetts-Bay ... A proclamation for a general fast : ... Thursday, the sixth day of April next ... Given at the Council-chamber in Boston, the second day of March, 1758 . (Printed by John Draper, printer to his excellency the governor and the honorable His Majesty's Council, 1758)
March 2, 1758 Proclamation by Governor Thomas Pownall for a day of prayer and fasting on April 6th in order to obtain blessings on the Protestant cause as well as the monarchy, and in supplication for sins.